Microstructure and chemical degradation of adobe and clay bricks - Calabria, Juliana A.; Vasconcelos, Wander L.; Boccaccini, Aldo R. (Ceramics International, 2009)
The environmental degradation of adobe and fired clay brick was studied. Leaching media based on Na2S2O5 solution and deionized water were used. The microstructure of the samples was evaluated by X-ray powder diffraction, nitrogen adsorption-desorption (BET method), Fourier transform infrared spectroscopy and scanning electron microscopy. The predominant phases detected were kaolinite and quartz for both the adobe and fired brick samples. The high surface reactivity, associated with a large amount of OH groups, contributes to the significant degradation of adobe. The fired clay brick showed a significant decrease in the average pore diameter after the first day of the leaching process; its specific surface area exhibited a reduction of about three orders of magnitude. The results of the present investigation contribute to a better understanding of the correlation between structure and leaching behaviour in adobe and clay brick, attending the renewed interest in these materials as environmentally attractive building blocks. © 2008 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.micros_8
Keywords: Adobes; B. Microstructure; B. Porosity; D. Clays; E. Structural applications